CDP Is a Repressor of Mouse Mammary Tumor Virus Expression in the Mammary Gland - Zhu, Quan (American Society for Microbiology, 2000)
Mouse mammary tumor virus (MMTV) transcription is highest in the lactating mammary gland but is detectable in a variety of other tissues. Previous results have shown that MMTV expression is suppressed in lymphoid and other tissues through the binding of the homeodomain-containing repressor special AT-rich binding protein 1 to a negative regulatory element (NRE) in the MMTV long terminal repeat (LTR). Another homeoprotein repressor, CCAAT displacement protein (CDP), also binds to the MMTV NRE, but a role for CDP in MMTV transcriptional suppression has not yet been demonstrated. In this paper, we show that the level of CDP decreases during development of the mammary gland and that this decline in CDP level correlates with the known increase in MMTV expression observed during mammary gland differentiation. Moreover, CDP overexpression was able to suppress MMTV LTR-reporter gene activity up to 20-fold in transient-transfection assays of mouse mammary cells. To determine if this effect was due to direct binding of CDP to the promoter-proximal NRE, we performed DNase I protection assays to map two CDP-binding sites from +835 to +845 and +920 to +931 relative to the first base of the LTR. Mutations engineered into each of these sites decreased CDP binding to the proximal NRE, whereas a combination of these mutations further reduced binding. Subsequently, each of these mutations was introduced into the full-length MMTV LTR upstream of the luciferase reporter gene. Analysis of stable transfectants of LTR constructs showed that CDP binding site mutations in the proximal NRE elevated reporter gene expression two- to sixfold compared to wild-type LTR constructs. Thus, MMTV expression increases during mammary gland development, in part due to decreased CDP levels and CDP binding to the LTR. Together, these experiments provide the first evidence that CDP acts as a repressor of MMTV transcription in the mammary gland.